PENGARUH PERBEDAAN SUHU PEREBUSAN DAN KONSENTRAS NaOH TERHADAP KUALITAS BUBUK TULANG IKAN GABUS (Channa striata) - Yunita Cucikodana; Agus Supriadi; Budi Purwanto (Universitas Sriwijaya, 2012)
The purpose of this research was to observe the quality of snake head fish bone powder using different boiling temperature and NaOH concentration.The Factorial Randomized Block Design was used with two factors of treatment and 2 replications. The different boiling temperatures (60 0C, 650C, 700C) and three different NaOH concentrations (Control 0%, NaOH 2%, NaOH 4% and NaOH 6%). The parameters were yield, whiteness, density, solubility and calcium content. The result showed that the treatments significantly effected the yield (43.98%-97.47%), whiteness (47.6-58.48%) density (0.51–0.67 g/ml), solubility(11.38-23.76%) and calcium content (16.86-22.77%). Keyword :bone powder, snake head, calcium